Isolation, Identification and Antimicrobial Activity of a Withanolide [WS-1] from the Roots of Withania somnifera - Kharel, Prakash; Manandhar, Mangala D; Kalauni, Surya K; Awale, Suresh; Baral, Janaki (Nepal Journal of Science and Technology, 2012)
Column chromatographic purification of the organic extract obtained from the roots of Withania somnifera yielded a biologically active withanolide compound WS-1 whose structure was established on the basis of spectroscopic evidences. Potent antibacterial activity was observed in this compound. DOI: http://dx.doi.org/10.3126/njst.v12i0.6497 Nepal Journal of Science and Technology 12 (2011) 179-186